IN QUEST OF THE INFORMATION SECTOR: MEASURING INFORMATION WORKERS FOR INDIA - Lal, Kashmiri (Malaysian Journal of Library and Information Science, 2005)
The paper is based on two 1981 and 1991 general censuses. The measurement of information workers and demarcation theory has been derived from Dordick and Wang. The paper makes comparisons of information workers for different countries from different regions during 1999, and subsequently focuses on the actual scenario on India. All the eleven categories of occupations notified by Government of India have been further refined into four main categories viz. information, production, service, and farms related workers. How information workers are skewed between rural and urban area, their performance on educational level, and place of working according to industry are the main findings of this research. India had approximately 39.4 million information workers during 1991 census, which worked out to be 13.78% of main workers (285.9 million). While most of the developed and few developing countries have achieved quite considerable proportion of the information workers, India's progress in this field is far away from encouraging.